IMPLEMENTATION OF THE FAMI BISYAUQIN AND TAKRIR METHODS IN IMPROVING AL-QURAN MEMORIZATION IN ISLAMIC BOARDING SCHOOLS - Silfia, Khalifatus; Herwati, Herwati (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
AThe desire to become a memorizer of the Qur'an is the dream of all students, but in memorizing activities, there are still many who are less motivated and have low enthusiasm for remembering; therefore, there must be an appropriate and easy method so that they achieve their goal perfectly, namely to become hafidz/hafidzah. This study aimed to analyze and examine the Implementation of the fami bisyauqin and takrir methods to improve the memorization of the Qur'an. The approach used is a descriptive qualitative case study type. Data collection using observation, interviews, and documentation. The location of this research is in the Islamic boarding school for women, Nurul Qur'an, Kraksaan. Data analysis techniques using data reduction, data presentation, concluding. The results of this study indicate that the Implementation of the fami bisyauqin memorization method is divided into seven parts until the end of 30 chapters, the first day of memorizing الفاتحةto النساء, the second day سورةالمائدةto التوبة, the third سورةto النحل, the fourth اسرائيل(الاسراء) to الفرقان, the fifth الشعراءto, the sixth الصافاتto الحجرات, and the seventh day قto الناس, the presence of the fami bisyauqin and takrir methods is a solution and a big wind to overcome the difficulties of memorizing the Qur'an. The implications of the application of the fami bisyauqin and takrir methods provide convenience in memorizing the Qur'an for memorizing the Qur'an and for the cleric who teaches it.